Centralization or decentralization? the impact of different distributions of authority on China's environmental regulation - Yang, Xiaohui; Yan, Ji; Tian, Kun; Yu, Zihao; Yu Li, Rebecca; Xia, Senmao (Technological forecasting & social change, 2021)
•To compare the effects of centralized and decentralized environmental governance.•To provide a solution to achieve a dual goal: economic growth along with environmental improvement.•To construct a two-level model to investigate the interaction among the central government, local governments, and local firms.•To examine the effects of information superiority of the central government in relation to the local governments on distribution of authority.•To propose a hybrid model to help cushion firms against high agency costs and local government–firm collusion. How to balance the central government and local governments’ political authority relating to environmental governance has long been a topic of intense debate in China. Since both environmental and economic regulations are regulatory tools of governments, political authority and systems must be considered in deciding to what extent to empower local governments. Central government needs to find a tradeoff point when being placed under the dual pressure of environmental protection and maintaining the economic growth rate. Based on a two-level principal–agent model, our research compares the effects of centralized and decentralized governance on the efficiency of environmental regulation. Our results suggest that under decentralized environmental governance, the local governments’ incentives increase, which results in either “race to the top” or “race to the bottom” competition in environmental regulation. Moreover, such governance prompts local governments to reduce their investment in economic development and environmental protection. However, decentralization in environmental governance will become more beneficial to the central government if the benefits of reducing information asymmetry surpass enhanced agency costs; otherwise, centralized environmental governance is preferred. Our research proposes a hybrid model of centralized and decentralized environmental governance to help cushion firms against high agency costs and local government–firm collusion.